Heart rate-index estimates aerobic metabolism in professional soccer players. Issue 12 (December 2020) - Colosio, Alessandro L.; Lievens, Maarten; Pogliaghi, Silvia; Bourgois, Jan G.; Boone, Jan
Abstract: Objectives: This study aimed at proposing a new heart rate (HR) method to track aerobic metabolism in soccer by: (i) validating a recently developed HR index (HRindex ) in professional soccer players, (ii) comparing HRindex vs the most common HR parameters and (iii) testing the agreement between measured and estimated VO2 values using HRindex . Design: cross-sectional. Methods: 184 professional soccer players performed a step incremental running test on a treadmill while VO2 and HR were recorded. HRindex was calculated (actual HR/resting HR) and its relationship with VO2 was compared with the relationships with the metabolism of actual HR, net HR, and % of HR reserve. Finally, HRindex was used to predict VO2 = ((HRindex · 6) − 5) · 3.5) and measured and estimated VO2 were compared by 2W RM-ANOVA and Bland–Altman analysis. Results: HRindex /VO2 relationship explained 85% of the variability in data, showing a higher performance than actual HR (77%) and similar values to the other parameters. Measured and estimated VO2 were not significantly different ≤14 km h −1, whereas at speeds ≥14 km h −1 measured VO2 was higher than estimated VO2 . Finally, measured and estimated VO2 were highly correlated ( R 2 = 0.85, p = 0.000), and showed no significant bias (bias = −1.03, z = −0.69, precision = 3.75 ml kg min −1 ). Conclusions: We validated the HRindex /VO2 relationship in professional soccer players. HRindex showed better agreement with metabolism than actual HR and similar agreement to the other HR parameters. HRindex allowed to estimate VO2, but at very high-intensity HRindex underestimated VO2 . Future studies should test this in real game conditions. HRindex could offer a time-efficient and easy-to-use "field" method to monitor aerobic metabolism in soccer.